ANALISIS PENYELESAIAN SENGKETA PEMILIHAN KEPALA DAERAH DALAM PUTUSAN MAHKAMAH KONTITUSI NOMOR 85/PUU-XX/2022 TERHADAP PEMBENTUKAN BADAN PERADILAN KHUSUS PEMILU DI INDONESIA - Nikmat Ilham; Mexsasai Indra; Muhammad A. Rauf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The regulations regarding the authority to settle regional election resultsgiven to the Constitutional Court have experienced several polemics. The problemthat arises is that the authority of the Constitutional Court (MK) to resolvedisputes over regional head election results is now permanent. This wasconfirmed in Decision Number 85/PUU-XX/2022 in which the Court stated thephrase "until the formation of a special judicial body" if a Special Judicial Bodycan be formed, of course by studying the paradigm and system of direct regionalelection dispute resolution that has been handled by the Constitutional Court. ,then perhaps this would be the best solution to "reduce" the burden on theConstitutional Court, whose ideals are focused on handling constitutionalproblems which are the authority and obligation of the Constitutional Court(Article 23 C paragraphs (1) and (2).This type of research can be classified into the type of normative legalresearch. This study used secondary data consisting of primary legal materials,secondary legal materials, tertiary legal materials and data collection techniqueswere carried out using the library study method.From the results of research on the problem, there are two main thingsthat can be concluded. First, resolving disputes over election results (election ofgovernors, regents and mayors) has experienced significant changes in practice.This expansion stems from the Constitutional Court's authority given by law inhanding down decisions, so that there is also an expansion of the applicant's legalposition, the object of the petition, case examination, evidence, as well asdecisions handed down by the Constitutional Court, the legal enforcement ofwhich has not yet been completed or has been completed but is ignored by theorganizers. Second, the ideal format for resolving the General Election ofRegional Heads Based on the Constitutional Court Decision Number 85/PUU-XX/2022 is ideally carried out by the Special Judiciary Agency.Keywords: Constitutional Court, General Election, Special Judicial Body